Um estudo semântico-enunciativo da palavra escravidão em dicionários de língua portuguesa - Dourado, Winnie Tathiane (2019)
From the concepts of the theory of Semantics of the Event, as proposed by Guimarães (2002), such as designation and rewriting, we propose to analyze the meaning of the word slavery in Portuguese language dictionaries. We have in mind that this object - the dictionary – is conceived as a linguistic instrument not excused from the reality, and, as Auroux (1992: 70) says, "it means that the appearance of linguistic instruments does not leave intact the human linguistic practices." Specifically, the objective of this dissertation is to answer the following questions: with the end of slavery, the meaning of this word and its uses have been affected? What, according to some dictionaries, did and does slavery mean? Based on these questions, the corpus of this dissertation is composed of lexicographic definitions from Portuguese language dictionaries that cover the periods of the 18th, 19th, 20th and 21st centuries. These dictionaries are printed and electronic, ranging from the Portuguese and Latin Vocabulary of Raphael Bluteau (1712 -1728), considered a landmark of Portuguese lexicography to the currently widely used digital version of the Houaiss Dictionary of the Portuguese Language from the Antônio Houaiss Institute ( 2009). At the end we can point out traits that characterize a lexicographic definition and throughout the analyzes we perceived a silencing of the black slavery in Brazil, what happens in the dictionaries during and after the slave period.